Regulation of redox signaling by reactive sulfur species - Kasamatsu, Shingo (J Clin Biochem Nutr, 2021)
Reactive sulfur species, such as cysteine persulfide, are produced endogenously at significant levels in cells and have rapidly emerged as common biomolecules. By virtue of improved analytical methods for detecting reactive persulfides, it has been demonstrated that these reactive molecules exhibit unique chemical properties and are present in various forms in vivo. Accumulating evidence has suggested that persulfides may be involved in a variety of biological processes, such as antioxidant and anti-inflammatory responses, biosynthesis of sulfur-containing molecules, mitochondrial energy metabolism via sulfur respiration, and cytoprotection via regulation of redox signal transduction induced by endogenous and exogenous electrophiles. Elucidation of the persulfide-dependent metabolism of redox signals is expected to facilitate our understanding of the importance of persulfides in regulating redox signals.